CAUSES OF AGING OF THE HUMAN BODY AND WAYS TO PREVENT EARLY AGING - Raxmatova Kumush Asror kizi (Academia Science Repository, 2023)
Researchers say that the active forms of oxygen that appear in human organs accelerate its aging process. Active forms of oxygen destroy all cellular components in the internal body and the cardiovascular system. The only remedy against this is said to be starvation. It is not for nothing that scientists have scientifically proven that fasting strengthens the immune system against diseases, and the number of cells that serve this purpose increases tenfold in a fasting person. Also, the higher the calorie content of the food consumed, the more active forms of oxygen more it increases. Therefore, it is advisable for those who want to live a long life to eat more wet fruits and vegetables together with low-calorie foods, and to drink juices, infusions of medicinal herbs and green tea.